AB0140 The role of raf kinase inhibitory protein in rheumatoid arthritis. (12th June 2018) - Cheon, Y.-H.; Suh, Y.S.; Yi, S.M.; Kim, M.; Lee, S.-I.; Noh, H.S.
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease of the joints and is characterised by immune cell infiltration, synovial hyperplasia, and destruction of cartilage and underlying bone 1 . Raf kinase inhibitory protein (RKIP), an endogenous inhibitor of the extracellular signal-regulated kinase (ERK) pathway, has been implicated as a suppressor of metastasis and NF-κB pathway in cancers 2 . Objectives: The NF-κB and ERK pathways are considered to be one of the most important pro-inflammatory signalling pathways in RA. Therefore, RKIP might be a potential therapeutic target for RA. However, whether and how RKIP regulates RA is not fully understood. The present study was performed to examine whether and how RKIP are differentially regulated in RA. Methods: The expressions of RKIP were assessed in synovial tissue, fluid and fibroblast-like synoviocytes (FLS) from patients with RA and osteoarthritis (OA) by immunofluorescence staining and western blotting. RA- or OA-FLS were infected with either a recombinant adenoviral RKIP overexpressing vector (Ad-RKIP) or shRNA-expressing vector (Ad-shRKIP). Control cells infected with a GFP-targeted recombinant adenoviral vector (Ad-shGFP) (figure 1C). And then, we investigated the effects of RKIP on the migratory activity and invasion rates of FLS by transwell migration and invasion assay. Results: Here, we show that RKIP expression is inversely correlated with RA. The levels of RKIP were significantly decreased in fibroblast-like synoviocytes (FLS), synovial fluid and synovium of RA patients compare to OA patients. And also find that migration and invasion of RA-FLS were significantly increased by the inhibition of RKIP compare to OA-FLS. Knockdown of RKIP in RA or OA-FLS resulted in a dramatic increase of MMP3 and IL6. We also found osteoclastogenesis of RAW cells were increased by the knockdown of RKIP. Conclusions: Our data identify a role of RKIP in RA and suggest that further studies on the potential involvement of RKIP will be beneficial in better understanding the pathology of and providing a new target for treatment for RA. References: [1] Ospelt C. Synovial fibroblasts in 2017. RMD Open2017;3(2):e000471. [2] Yesilkanal AE, Rosner MR. Raf kinase inhibitory protein (RKIP) as a metastasis suppressor: regulation of signaling networks in cancer. Crit Rev Oncog. 2014;19:447–454. [3] Noh HS, Hah YS, Ha JH, Kang MY, Zada S, Rha SY, Kang SS, Kim HJ, Park J, Byun J, Hahm JR, Shin JK, Jeong S, Lee Y, Kim DR. Regulation of the epithelial to mesenchymal transition and metastasis by Raf kinase inhibitory protein-dependent Notch1 activity. Oncotarget2016;7(4):4632–46. Disclosure of Interest: None declared